Is there a best model? A radioecological case study - Tarsitano, Davide (2005)
Mathematical models are extensively used to support decision-making in many disciplines. Nevertheless there are not clear standard guidelines to assess models performance. This significantly affects model selection processes, which aim to determine the "best model", among several possible candidates.